Efficacy of Early Combination Therapy With Lianhuaqingwen and Arbidol in Moderate and Severe COVID-19 Patients: A Retrospective Cohort Study - Fang, Jie; Li, Hui; Du, Wei; Yu, Ping; Guan, Ying-Yun; Ma, Shi-Yu; Liu, Dong; Chen, Wei; Shi, Guo-Chao; Bian, Xiao-Lan (Frontiers in Pharmacology, 2020)
Objective: Since the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan City, China, coronavirus disease 2019 (COVID-19) has become a global pandemic. However, no special therapeutic drugs have been found for COVID-19 until now. The aim of this study was to search for effective drugs for COVID-19 treatment. Materials and Methods: We conducted a retrospective cohort study with a total of 162 adult inpatients (≥18 years old) from Ruijin Hospital (Shanghai, China) and Tongji Hospital (Wuhan, China) between Jan 27, 2020 and Mar 10, 2020. The enrolled COVID-19 patients were first divided into the LHQW monotherapy group and the LHQW+ arbidol combined therapy group. Then, these two groups were further classified into moderate and severe groups according to their COVID-19 clinical classification. Results: The early combined usage of Lianhuaqingwen (LHQW) and arbidol can significantly accelerate the recovery course of patients with moderate COVID-19 by reducing the time of nucleic acid negative conversion, the time of chest CT improvement and the length of hospital stay. However, in patients with severe COVID-19, no benefit was observed in patients treated with LHQW+ arbidol combined treatment. In this study, both arbidol and LHQW were well tolerated without serious drug-associated adverse events. Conclusion: The early combined usage of LHQW and arbidol may accelerate the recovery course and improve the prognosis of patients with moderate COVID-19.